The Difference of Landslide-Prone Areas Between Heuristic and Statistical Methods in Lima Puluh Kota Regency - Ahyuni, Ahyuni -; Susetyo, Bigharta Bekti; Oktari, Fadhilla; Nur, Hamdi; Aziz, Azwirda (Sumatra Journal of Disaster, Geography and Geography Education, 2021)
Measurement of landslide area can be done by heuristic, statistical or deterministic methods. This article will discuss the differences between the results of the two approaches, heuristic method and the statistical method at a scale of 1: 50,000 in Lima Puluh Kota Regency as one of the regencies in West Sumatera Province that often experiences landslides. The heuristic method is measured based on the rules outlined in the Indonesian disaster risk book (RBI) issued by the National Disaster Management Agency, while the statistical method uses the bivariate WoE (weight of Evidence) method with the variables used as determinants of landslide occurrence. The results of this study indicate that the use of heuristic methods and statistical methods shows different results in several areas regarding the high and low probability of landslide events.